0626 Nocturnal Pulse Event Frequency in Multiple System Atrophy: An Exploratory Pilot Study. (25th May 2022) - McCarter, Stuart; Coon, Elizabeth; Benarroch, Eduardo; Louis, Erik St
Abstract: Introduction: Risk of sudden death in multiple system atrophy (SuD-MSA) is greatest during sleep. Mechanisms underlying SuD-MSA may involve impaired brainstem arousal and cardiovascular responses to hypercapnia in MSA patients. We hypothesized that nocturnal arousal-related tachycardia events are reduced in MSA patients. We analyzed whether nocturnal pulse event frequency was altered in patients with MSA compared to patients with sleep disordered breathing without MSA utilizing portable overnight oximetry. Methods: We retrospectively analyzed 46 probable MSA and 46 age-sex matched patients with sleep disordered breathing (SDB) without MSA, excluding patients receiving cardioactive medications. Nocturnal oxyhemoglobin desaturation indices (ODI) and pulse event indices (PEI) were automatically recorded for all patients using portable overnight oximetry. We calculated a PEI/ODI ratio to determine the relationship between probable breathing-related arousals and pulse rate change. Cardiovagal function was assessed by heart rate to deep breathing and Valsalva ratio in patients with MSA and Composite Autonomic Severity Score was assigned. Group comparisons were made with non-parametric tests. Multivariable regression explored relationships between oximetry variables and clinical characteristics. Results: Average age at overnight oximetry was 62.9 ± 7.7 years. Total respiratory events between MSA patients compared with OSA controls were similar (95.0 ± 118.6 vs 73.5± 54.2, p=0.61). Total pulse events were lower in MSA than OSA controls without MSA (25.5±44.2 vs 111.6±120.2, p<0.001), as were pulse events per hour (3.1 ± 5.3 vs. 12.8 ± 10.8, p <0.001). The ratio of PEI/ODI was lower in MSA than OSA patients without MSA (p<0.001). Twelve (26%) MSA patients had zero pulse rate events, while all OSA patients without MSA had at least 1 pulse rate event (p<0.001). The number of pulse events was not associated with severity of cardiovagal dysfunction on daytime autonomic function testing. Conclusion: Patients with MSA have fewer pulse rate events when compared with SDB patients without MSA, despite similar overall respiratory event frequency. The number of pulse events was not explained by severity of daytime autonomic dysfunction in those with MSA. Whether nocturnal pulse event response to sleep disordered breathing is a marker of disease severity or plays a role in SuD-MSA deserves further study. Support (If Any):